Sistemática de seleção de servidores para as funções de confiança, baseada na abordagem das competências - Picolini, Ana Claudia (2015)
Aiming to contribute to a process of servants’ selection for rewarded positions (positions of trust) more rational and sustainable in the public context, the general goal of this research was to propose a systematic to the servants’ selection for the positions of trust, according to the competency-based approach. The method used was action-based research and the studied organization was Votuporanga Campus of the Federal Institute of Education, Science and Technology of São Paulo. The results achieved were the development of a systematic to the selection of servants, which included mapping processes of the work, the competencies mapping and the development of a Selection Matrix. From the results obtained and the theoretical discussion it was possible to conclude that the selection systematic proposal may contribute to the selection process rationalization of servants by providing insights according to the competency-based approach. It also minimizes the use of subjective preferences criteria for the position of trust designation, through the establishment of selection mechanisms based on competencies and the servant work situation in positions of trust to be occupied, respecting the appointment and resignation freedom that the law assures to the holder of nominating power.